The effects of repeated delivery of angiotensin II AT(1) receptor antisense on distinct vasoactive systems in Ren-2 transgenic rats: young vs. adult animals - Vaněčková, Ivana; Dobešová, Zdenka; Kuneš, Jaroslav; Zicha, Josef (Hypertension research, 2012)
Although Ren-2 transgenic rat (TGR) is defined as a model of angiotensin II-dependent hypertension, we studied whether the renin-angiotensin system (RAS) is really the main contributor to blood pressure (BP) elevation in hetero- and homozygous TGRs. Moreover, we examined whether repeated antisense (AS) therapy against AT(1) receptors would have a similar effect on the BP and the contribution of the principle vasoconstrictor/vasodilator systems to BP regulation in young and adult TGRs. From the age of 30 (young) and 100 (adult) days, rats were injected with AS for 40 days in 10-day intervals. After 10 and 40 days of AS therapy, the basal BP and acute BP responses to the sequential blockade of the RAS, sympathetic nervous (SNS) and nitric oxide systems were determined in conscious rats. The RAS system was the major system maintaining elevated BP in young homozygous animals, whereas there was an increasing contribution of the SNS in heterozygous TGR with age. The AS therapy in the young TGR had a transient BP-lowering effect that was associated with reduced cardiac hypertrophy; the AS therapy was most effective in young homozygous TGR, causing a substantial reduction of angiotensin-dependent vasoconstriction. In heterozygous rats, AS therapy at earlier stages was related to an inhibition of sympathetic vasoconstriction, whereas to RAS inhibition in established hypertension. In conclusion, repeated AS therapy had transient antihypertensive effects exclusively in young TGR. The contribution of the RAS to BP maintenance is highly important only in homozygous TGRs, whereas it is surpassed by SNS in heterozygous TGR.
Keywords: receptor angiotensinu typ 1; vazokonstrikce; Aging; Rats; Homozygote; Receptor, Angiotensin, Type 1; Cardiomegaly; Heterozygote; Oligonucleotides, Antisense; Hypertension; Vasoconstriction; Disease Models, Animal; mužské pohlaví; kardiomegalie; renin-angiotensin systém; krysa rodu Rattus; Rats, Transgenic; věkové faktory; antihypertenziva; Antihypertensive Agents; stárnutí; Animals; modely nemocí na zvířatech; zvířata; oxid dusnatý; antisense oligonukleotidy; Nitric Oxide; Renin-Angiotensin System; hypertenze; homozygot; sympatický nervový systém; Sympathetic Nervous System; Age Factors; potkani transgenní; Male; heterozygot